2017
DOI: 10.1111/gwao.12202
|View full text |Cite
|
Sign up to set email alerts
|

‘Show us your frilly, pink underbelly’: Men administrative assistants doing masculinities and femininity

Abstract: Research on men tokens (or numerical minorities) at work has focused on the processes by which men try to claim hegemonic masculine identities for themselves and how workplace interactants support or reject these attempts. In contrast to masculinity studies, token theory has paid less attention to non‐hegemonic masculinities. Using interviews with men administrative assistants, I develop a more comprehensive understanding of men tokens' gender performances and their significance for gender inequality. I presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
8
0
2
Order By: Relevance
“…Recent scholarship has argued that we are witnessing ‘inclusive masculinity’ with a ‘softening’ of gender codes, more emotional expression, a reduction in hierarchy and greater diversity in valued masculinities (Anderson & McCormack, 2018). Similarly, ‘hybrid masculinity’ incorporates femininities and may even appropriate them ‐ reinforcing rather than challenging masculinity (Arxer, 2011; Bridges & Pascoe, 2014; Heath, 2003) suggesting the shift to alternative masculinities should not be overstated (see also: Seeley, 2018).…”
Section: The Identity Constructedmentioning
confidence: 99%
“…Recent scholarship has argued that we are witnessing ‘inclusive masculinity’ with a ‘softening’ of gender codes, more emotional expression, a reduction in hierarchy and greater diversity in valued masculinities (Anderson & McCormack, 2018). Similarly, ‘hybrid masculinity’ incorporates femininities and may even appropriate them ‐ reinforcing rather than challenging masculinity (Arxer, 2011; Bridges & Pascoe, 2014; Heath, 2003) suggesting the shift to alternative masculinities should not be overstated (see also: Seeley, 2018).…”
Section: The Identity Constructedmentioning
confidence: 99%
“…In China, researchers have shown that when their masculinity was called into question at work, some men turned to the realms of fatherhood and family to construct a respectable manhood (Choi & Peng, 2016; Lin, 2019). Other scholars have examined the strategies men use to preserve their manliness in jobs that challenged their masculinity (Cross & Bagilhole, 2002; Johnston & Hodge, 2014; Seeley, 2017). For example, studies have explored the experience of men in women‐dominated occupations such as nursing, clerical work, domestic work, and low‐paid interactive service work (Näre, 2010; Solari, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cross and Bagilhole (2002) examined how men in “women's jobs” either distanced themselves from female colleagues to preserve a traditional masculinity or reconstructed a different masculinity by identifying with their job. Seeley, (2017) presented a four‐part typology of hegemonic masculinity, alternative masculinity, critical masculinity and male femininity to understand how male administrative assistants performed their token status. Another body of research has explored men in masculinized occupations such as the military, policing, and firefighting (Lee et al., 2019; Perrott, 2019; Reid et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mesner (1992) defende que crianças traçam seus perfis escolares com base em conceitos impostos pela sociedade e exemplifica: dentre meninos e meninas com excelentes desempenhos em ciências exatas, cinco entre dez meninas escolherão uma área científica de estudo ao iniciarem a carreira profissional, ao passo que sete entre dez meninos optarão por seguir carreiras científicas. Isto reforça a afirmação de Blanchard, Orange e Pierrel (2016), que alegam que meninas são excluídas de carreiras científicas e, segundo Gabay-Egozi, Shavit e Yaish (2014), optam por profissões em ciências não exatas, por atribuírem menor utilidade (BENBOW et al, 2000;CECI et al, 2014) Ainda sobre a segregação sexual no contexto estadunidense, Hughes (1958) e Dubar (1997) Kanter (1977) e Seeley (2018), um dado local de trabalho é profundamente impactado pelas diferentes identidades sociais ali presentes, tais como raça e gênero. Assim, quando um grupo de indivíduos compreende menos de 15% de uma categoria de trabalho, eles são identificados como tokens (KANTER, 1977, p. 208).…”
Section: Estereótipos De Gênero No Mercado Produtivo: Carreiras Feminunclassified
“…Na prática, raríssimas são as oportunidades de ascensão entre esta função e funções de gestão, o que obriga os indivíduos que almejam ascender na hierarquia organizacional a mudarem sua área de atuação. Mudanças na perspectiva de carreira destes profissionais são, normalmente, resultados de realocações em diferentes áreas das empresas, o que confere a estes profissionais, além do acúmulo de funções, uma movimentação fundamentalmente lateral, em vez de vertical (KANTER, 2008;SEELEY, 2018).…”
Section: Estereótipos De Gênero No Mercado Produtivo: Carreiras Feminunclassified